The roots of 21st century Malay anger: When young men and women come to the fore - Dina S. Zaman (International Journal of Interreligious and Intercultural Studies, 2021)
This article seeks to explain briefly to the reader about far right nationalist movements in Malaysia. While this is not a recent occurrence, it spiked during the time of Pakatan Harapan, the Opposition bloc that won the 13th Malaysia General Elections. Seeing non Malay/Muslim faces in the new government frightened many, even those who were against the former Barisan Nasional government. The paper is based on my current research on Malay youth identity of both genders, who are pushing the Malay narrative to the fore, as they demand their rights as Malays; Covid 19 has shown that economic opportunities are getting more scarce. The people I am studying and have spoken to feel that they have low social capital, and their uneasiness at seeing minority communities ‘thrive’ in Malaysia. What is causing this fear? This article posits economic reasons.